Agora: collaborative tool for the creative practices - Hipwell, Samuel (2014)
This project will discuss what is needed in a tool to allow artists to collaborate with each other in an effective manner. This project will go through related research and discuss the results of the investigation, with the aim of finding the usability needs for an artist collaboration using digital tools. The aim of an artist collaboration, is to pool their collective knowledge and resources into a single form by the use of different dialogue. I will be questioning what mechanisms are produced from these dialogues, and how do they allow a collaborations to work efficiently together? From these understandings the aim is to develop a set of requirements which is needed to allow for an artistic collaboration to practice over a digital medium.